2011
DOI: 10.1007/s13592-011-0087-8
|View full text |Cite
|
Sign up to set email alerts
|

Diel nectar secretion rhythm in squash (Cucurbita pepo) and its relation with pollinator activity

Abstract: Most studies of foraging behavior in bees have been performed under artificial conditions. One highly neglected area is the daily nectar secretion rhythm in flowers including how nectar properties may vary with time of day. As a first step in understanding the connections between forager behavior and nectar presentation under more natural conditions, we examined nectar secretion patterns in flowers of the squash Cucurbita pepo. Under greenhouse conditions, squash flowers exhibit consistent diel changes in nect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 45 publications
(48 reference statements)
2
19
0
Order By: Relevance
“…In the squash, Cucurbita pepo L., nectar volume and concentration varies significantly during the course of the day and this have influence on when honey bees visit its flowers (Edge et al 2012). This also seems to be the case for O. maculata, in which nectar volume and concentration also varies throughout the day and there is a positive correlation between nectar volume and the frequency of visits by Heliconius butterflies.…”
Section: Discussionmentioning
confidence: 96%
“…In the squash, Cucurbita pepo L., nectar volume and concentration varies significantly during the course of the day and this have influence on when honey bees visit its flowers (Edge et al 2012). This also seems to be the case for O. maculata, in which nectar volume and concentration also varies throughout the day and there is a positive correlation between nectar volume and the frequency of visits by Heliconius butterflies.…”
Section: Discussionmentioning
confidence: 96%
“…A honey bee forager will remember the time of day it exploited a profitable food source and will return to that source at approximately the same time on the following day (von ButtelReepen, 1900;Beling, 1929;Wahl, 1932;Wahl, 1933;Renner, 1955;Renner, 1957;Beier, 1968;Beier and Lindauer, 1970;Frisch and Aschoff, 1987;Moore and Rankin, 1983;Moore et al, 1989). This time memory enables bees to match their foraging efforts with nectar secretion rhythms of flowers by cuing on either the time of highest nectar concentration (Butler, 1945;Corbet and Delfosse, 1984;Kleber, 1935) or highest total sugar (Giurfa and Núñez, 1992;Rabinowitch et al, 1993;Edge et al, 2012). This means that many foragers do not start their day as novices: the time memory eliminates the need to expend excess energy required to rediscover the same food sources each day.…”
Section: Introductionmentioning
confidence: 99%
“…Honey bees, Apis mellifera, have the remarkable ability to remember the time of day when food sources are most profitable. This time-memory, also described as circadian time-place learning (cTPL), has been shown repeatedly in A. mellifera (Butler, 1945;Corbet and Delfosse, 1984;Edge et al, 2012;Giurfa and Núñez, 1992;Kleber, 1935;Rabinowitch et al, 1993) and has now been demonstrated in the ants Ectatoma ruidum (Schatz et al, 1999) and Paraponera clavata (Harrison and Breed, 1987) and in the stingless bees Melipona fasciculata (de Jesus et al, 2014), Trigona amalthea (Breed et al, 2002) and Trigona fulviventris (Murphy and Breed, 2008). Evidence that honey bee time-memory is driven by a circadian clock comes from (1) experiments showing a free-running period of foraging behavior close to 24 h under constant conditions (Frisch and Aschoff, 1987;Renner, 1955Renner, , 1957, (2) phase shifts, with transients, in response to phase changes in light-dark (LD) cycles (Beier, 1968;Renner, 1959) and (3) a limited range (20-26 h) of entrainment under LD cycles (Beier, 1968).…”
Section: Introductionmentioning
confidence: 83%